Curriculum framework for preparing quality teachers for the future: Developing guiding principles - Ratnavadivel, Nagendralingan; Hoon, Chang Lee; Salih, Maria; Karuppiah, Nagalingam; Omar, Ainon; Md. Yassin, Sopia; Dawi, Amir Hasan; Saad, Noor Shah; Mohamed Hashim, Abdul Talib (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Globalization is constantly impacting on education and is radically transforming it in terms of the mode and culture of learning. The shift from product-economy to knowledge-economy has profound implications for the kind of education a nation has to offer its future generation. The need for knowledge workers places emphasis on new attributes for learners, particularly those which pertain to twenty-first century skills. The last decade and a half has also seen the emergence of international student ranking lists such as TIMSS, PISA, PIRLS, Olympiads, which have put tremendous pressure on education ministries. A response to this pressure of „rank and shame‟ has been a flurry of education reform initiatives, including in Malaysia. The ability to develop learners who can think critically and creatively and to reason logically and to innovate is the challenge in education. The Malaysia Education Blueprint 2013-2025 has identified teacher education among the eleven shifts to transform the Malaysian education system. This paper will discuss how guiding principles for a teacher education curriculum frameworkis being developed in line with national needs and demands of international trends. Focus on teacher education would directly involve an investigation of teacher education curriculum, namely its planning, management and development. This concern is imperatively linked to the values, skills and knowledge of teachers. A teacher education curriculum frameworkneeds to strike a balance between standardization and allowing for flexibility and creativity so that teacher education does not stifle the creativity and holistic growth of teachers and their students.